Asserting Religious Text in the Modern World - Mazen Hashem (International Institute of Islamic Thought, 2010)
The khutbah delivered each Friday in mosques represents an important facet of the Muslims’ religious imagination. Islam, being an ultra-scriptural religion, requires that those who deliver this sermon, the khatib, engage in a wide range of creative handling of texts. The khutbah stands as concentric circles of belonging to a text-rooted religion and to the continuous realignment of those texts when addressing social reality; the khatib stands as an interpreter of lived experiences as well as a maker and shaper of such experiences. The quest of relevance in the khutbah is counterbalanced by the quest for authenticity. This discourse analysis study, which analyzes two years’ worth of khutbahs delivered in Southern California, focuses on three interrelated dimensions of khutbahs: how certain texts assert their authority, the different approaches to contextualizing the text, and how texts are reinterpreted in the face of the challenges of modernity.